Dimensi Sosial dalam Literasi Anak pada Platform Sibi: Integrasi Pendidikan Karakter Berbasis Profil Pelajar Pancasila dan Implikasinya terhadap Pembelajaran - Candra, Lila Ayu; Setiawati, Eti; Syaiful Rizal, Maulfi; Islahuddin, Islahuddin (Hasta Wiyata, 2026)
This study aims to analyse the social dimensions in children’s reading books on the Indonesian Book Information System (SIBI) platform, to identify the character education values contained within the texts, and to examine their integration with the Pancasila Student Profile and their implications for Indonesian language learning in primary schools. This study employs a qualitative approach using a descriptive method to analyse the children’s storybook *Nanti Saja* by Fransisca Emilia, which falls within the early reader category B3. The research data consists of excerpts from the text representing social dimensions and character education values, collected through document analysis and analysed using the Miles and Huberman model. The research findings indicate that the social dimension in the text is represented through the interactions of characters within family, friendship and community settings, which function as spaces for contextual character formation. Eight dominant character education values were identified: honesty, discipline, hard work, creativity, curiosity, communication, environmental care and social care. These values are not presented normatively but are internalised through the characters’ actions and social experiences within the stories. Furthermore, these character education values are linked to the dimensions of the Pancasila Student Profile, particularly in the aspects of mutual cooperation, faith and noble character, critical thinking, creativity, and global diversity.